2010
DOI: 10.1093/chemse/bjq076
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Odor Detection Threshold in the Gottingen Minipig

Abstract: The aim of the study was to examine the ability of Göttingen minipigs to acquire an olfaction-based operant conditioning task and to determine the detection threshold for ethyl acetate and ethanol. We used an automated olfactometer developed for rodents to train and test 14 pigs. Odor sampling and reliable responding were obtained after three to fifteen 160-trial sessions. Successful transfer of the task from ethyl acetate to ethanol was achieved in 1–4 sessions. Detection threshold for ethyl acetate varied be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The only study of greater significance was carried out using Göttingen minipigs (Sus scrofa domestica). The ODTs for ethyl acetate and ethanol were determined as a concentration as low as 5 ppm (Sondergaard et al 2010), which is far from the lowest ODT reported in other mammalian species, but it is important to point out the inconsistencies in methodology. As experiments in these species are still in their infancy, they are focused on the ability of determination, in contrast with olfactory threshold experiments in primates, dogs, or rodents.…”
Section: Other Mammalian Speciesmentioning
confidence: 98%
“…The only study of greater significance was carried out using Göttingen minipigs (Sus scrofa domestica). The ODTs for ethyl acetate and ethanol were determined as a concentration as low as 5 ppm (Sondergaard et al 2010), which is far from the lowest ODT reported in other mammalian species, but it is important to point out the inconsistencies in methodology. As experiments in these species are still in their infancy, they are focused on the ability of determination, in contrast with olfactory threshold experiments in primates, dogs, or rodents.…”
Section: Other Mammalian Speciesmentioning
confidence: 98%
“…6), and some Ungulate species are legendary for their olfactory abilities [Keller and Lévy, 2012], but only a few studies have actually measured their olfactory sensitivity. One strain of pigs surpassed the olfactory sensitivity of Primates and rats for 1 odorant (alcohol) but not another (ethyl acetate) [Søndergaard et al, 2010]. So it is not clear if the somewhat DOI: 10.1159/000509579 larger cVF of the piriform area in Ungulates results in greater olfactory sensitivity.…”
Section: Piriform Areamentioning
confidence: 99%
“…The domestic miniature pig represents an attractive alternative even though similar studies of ageing pigs have not been published and it is not known if, or at what age, AD‐like pathology might develop. Validated behavioural tests are well established for disease‐associated mental changes , as are imaging procedures , and it is relatively simple, during sedation, to tap from the cisterna magna a few millilitres of cerebrospinal fluid (CSF) . The identity between human and porcine APP is very high, with identical secretase cleavage sites, and the porcine brain is capable of increased production of Aβ40 and Aβ42 identical to the human fragments .…”
Section: Current Genetically Modified Pig Models For Human Ndsmentioning
confidence: 99%